The Belief System Serves as a Disaster Mitigation Mechanism to Preserve the Local Wisdom of the Baduy Tribe - Afifatul A'la; Mukminan Mukminan; Dedes Senja Anisfa; Annisa Priantari Putri; Wahyu Farida (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
This research aims to explore the belief system that serves as a disaster mitigation strategy in preserving the local wisdom of the Baduy tribe. It is a qualitative study conducted through data collection techniques such as observation, interviews, and documentation. The research findings indicate that the Baduy tribe, residing in the Kendeng Mountains of Banten, faces an uneven and disaster-prone environment, including landslides, floods, forest fires, and environmental degradation. The belief system embraced by the Baduy tribe is known as â€œSunda Wiwitan.â€ It is characterized by the presence of â€œpikukuhâ€ which serves as a guidelinefor the communityâ€™s interaction with the natural environment. These â€œpikukuhâ€ consist of rules that emphasize the importance of preserving the naturalÂ  environment without any alteration. The philosophy contained within the â€œpikukuhâ€ includes statements such as â€œLojor teu menunangÂ dipotong, pondok teu meunang disambungâ€, â€œGunung teu meunang dilebur, lebak teu meunang di rusakâ€, and â€œBuyut teu meunang dirobah, larangan teu meunang dirempak.â€ Each of these philosophies teaches the importance of preserving the environment as a form of disaster mitigation for the Baduy tribe.